Staffing of small nonprofit organizations: A model for retaining employees - Lise Anne Slatten; Joshua S. Bendickson; Meagan Diamond; William C. McDowell (Journal of Innovation & Knowledge (JIK), 2021)
Small nonprofit organizations (SNPOs) are a large part of the growing nonprofit sector. These nonprofit organizations (NPOs) generally receive 100,000-250,000 in annual revenue. These entities operate similarly to for-profit businesses, with a mission, values, and dependable employees. One factor that sets SNPOs apart from for-profit organizations is the ability that for-profit entities have to provide higher, more competitive wages and better benefit packages for employees. NPOs often lack this ability, which can result in staffing challenges and high turnover rates. This study explores the different ways these NPOs attract employees, the types of incentives or benefits offered, and what can help retain employees once they are hired. The concept of employee commitment is also explored in the context of SNPOs. This information can provide SNPOs with a better understanding of talent acquisition and retention strategies that can lead to improved operational and strategic planning.
Keywords: 650; Employee commitment; Employee retention; Nonprofit organizations; Turnover